Fructose and Non-Alcoholic Steatohepatitis - Roeb, Elke; Weiskirchen, Ralf (Frontiers in Pharmacology, 2021)
Background: The excessive consumption of free sugars is mainly responsible for the high prevalence of obesity and metabolic syndrome in industrialized countries. There is growing evidence that fructose contributes to the development and severity of non-alcoholic fatty liver diseases (NAFLD). In epidemiologic studies, energy-adjusted higher fructose intake was associated with NAFLD in adolescents with obesity. In addition to glucose, fructose, as an equivalent component of conventional household sugar, appears to have negative metabolic effects in particular due to its exclusive hepatic metabolism. Since fibrosis stage predicts liver-associated mortality, cardiovascular diseases are still the major overall cause of mortality in patients with non-alcoholic liver diseases and associated steatohepatitis (NASH). The aim of this review is to summarize the current research supporting a role for dietary fructose intake in the progression of liver fibrosis and life expectancy in NASH. Method: Selective literature search in PubMed using the keywords ‘non-alcoholic fatty liver’, ‘fructose’, and ‘fibrosis’ was conducted. Results: The rate of overweight and obesity is significantly higher in both, adult and pediatric NASH patients. The consumption of free sugars is currently three times the maximum recommended amount of 10% of the energy intake. The current literature shows weight gain, negative effects on fat and carbohydrate metabolism and NASH with hypercaloric intake of fructose. Conclusion: Excessive fructose consumption is associated with negative health consequences. Whether this is due to an excess of energy or the particular metabolism of fructose remains open with the current study situation. The urgently needed reduction in sugar consumption could be achieved through a combination of binding nutritional policy measures including taxation of sugary soft drinks. Studies support the concept that dietary fructose intake, in excess of that normally consumed in fruits and vegetables, may alter hepatic metabolism in favor of lipogenesis. Overall, results indicate that further research is warranted into the potentially protective role of a lower fructose diet in the development of NAFLD in adolescents and adults.